Exploring Indigenous food sovereignty and food environments characteristics through food interventions in Canada: a scoping review - Fabrice Mobetty; Malek Batal; Valérie Levacher; Ines Sebai; Geneviève Mercille (International Journal of Circumpolar Health)
Indigenous food sovereignty (IFS) has the potential to reconnect Indigenous peoples in Canada to their food systems, reduce health problems and improve food security. Using PRISMA-ScR guidelines to search Medline, Web of Science, Embase and Cabi databases, this review sought to explore the characteristics of IFS promotion and the food environments involved through food and nutrition interventions in Indigenous communities in Canada. Data from 30 relevant studies published between 2004 and 2022 were included, analysed and synthesised using a thematic approach based on key IFS principles and a food environment typology. Most studies were conducted in urban contexts, mainly in provinces with the largest Indigenous populations. Local descriptions of IFS showed conceptual and operational similarities. Among the four key principles of IFS, the principle of participation was the most reported. Gardening, farming, hunting, fishing and gathering were the main food activities used to operationalise IFS in traditional and cultivated food environments. Several IFS facilitators and barriers were identified. The IFS movement that emerged from the literature in Canada advocates for a healthy and sustainable food system based on traditional beliefs and controlled by communities to ensure wellbeing and food security. This review provides evidence of converging visions for food autonomy despite the heterogeneity of Indigenous nations in Canada.